Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
a = 4
b = -2
Step-by-step explanation:
If the given function is continuous at x = 1
[tex]\lim_{x \to 1^{-}} f(x)=(x+1)[/tex]
[tex]=2[/tex]
[tex]\lim_{x \to 1^{+}} f(x)=ax+b[/tex]
[tex]=a+b[/tex]
[tex]\lim_{x \to 1} f(x)=ax+b[/tex]
[tex]=a+b[/tex]
And for the continuity of the function at x = 1,
[tex]\lim_{x \to 1^{-}} f(x)=\lim_{x \to 1^{+}} f(x)=\lim_{x \to 1} f(x)[/tex]
Therefore, (a + b) = 2 -------(1)
If the function 'f' is continuous at x = 2,
[tex]\lim_{x \to 2^{-}} f(x)=ax+b[/tex]
[tex]=2a+b[/tex]
[tex]\lim_{x \to 2^{+}} f(x)=3x[/tex]
[tex]=6[/tex]
[tex]\lim_{x \to 2} f(x)=3x[/tex]
[tex]=6[/tex]
Therefore, [tex]\lim_{x \to 2^{-}} f(x)=\lim_{x \to 2^{+}} f(x)=\lim_{x \to 2} f(x)[/tex]
2a + b = 6 -----(2)
Subtract equation (1) from (2),
(2a + b) - (a + b) = 6 - 2
a = 4
From equation (1),
4 + b = 2
b = -2
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.